El derecho de alimentos innumerado art. 2 (127), régimen de visitas y su incongruencia con los principios de simplificación y economía procesal consagrados en el artículo 169 de la constitución de la república - Freire España, Edgar Mesias (2015)
This legal research revolves around the problems arising from procedural food at trial, the defendant in unique audience that has as aims to establish a alimony in favor of child or adolescent; it may also demand the right to visits to relate with their children affectively, thereby giving fulfillment to the Constitutional principles of simplification and procedural economy consecrated in the article 169 of the Constitution of the Republic of Ecuador. Within the present study discusses essentially the responsibility of the parents towards their children and the right of children to know the parents and maintain relationships with them and there the best interests of the child or adolescent as a principle that prevails in the Ecuadorian law all based on compliance with the constitutional principles set out in Art 169 of the Constitution of the Republic. It is claimed that from the rights in the Convention on the Rights of the Child, Ecuador is responsible for enforcing compliance of the rights enshrined in the international instrument, the Convention became the starting point for the development historic fundamental rights of children and adolescents, and the reference to define the national laws and legislative measures, both for the construction of equal treatment in law and defend the respect of human rights of this group of vulnerable people, considering them not as objects of law, but as rights holders. With the enactment of the Code of Children and Adolescents and the Constitution in 2008, is where the state guarantees the protection and development of the child and adolescent, administrative measures, economic and legal order to be effective. However, the July 28, 2009 is published in Official Register Nro.643 the Organic Code Reform Act of Childhood to Adolescence, Book II, Title V of the law in relation to food and the right to visits is subject to that determines the Title IV of the Code of Children and Adolescents in 2003, meaning that there are two different actions considered to exercise their rights. During the course of this investigation demonstrated that the procedure legally, on the right to food and right to visits when considered separately for processing is inconsistency with the principles of simplification and procedural economy consecrated in the Constitution. This research is based by performing a field study regarding the problem to investigate, to what has been obtained the judgment of a panel of judges of the courts for children and adolescents and Civil Courts are competent to hear matters in children by interview technique and practice free lawyers, plaintiffs and defendants in cases of food and visits by the survey technique, who have expressed their views and opinions regarding the proposed theme. It also complements the study with the drawing of conclusions, recommendations and the respective legal reform proposal unnumbered article right food 2 of the Organic Code of Childhood and Adolescence.